The Validity of an Innovative Image Processing Method to Measure Q Angle in Supine Position - mohammad rahimi; naser Mahrshad (Sport Sciences and Health Research)
Q angle variation has been reported as the most important factor in patellafemoral pain syndrome in many researches. The purpose of this study was to design and determine the validity of a new Q angle measurement method in supine position. This method calculated the Q angle by processing those images captured from lower extremity. For this purpose, 18 subjects (age23.55±2.24 years, weight 73.00±10/47 kg, and height 175.77±8.28 cm) were selected to participate in this study. The innovative image processing and CT scan methods were used to calculated the Q angle in supine position. Pearson’s correlation coefficient was used to estimate the correlation between these two methods. The results indicated a significant relationship (P=0.001) between Q angles obtained by innovative image processing method and CT scan method (r=0.92). Based on these findings, the innovative image processing method had a high correlation with CT scan method in Q angle measurement in supine position. It can be concluded that the innovative image processing method can be used as a method with high accuracy along with other methods to measure Q angle.